2022
DOI: 10.3390/antiox11020420
|View full text |Cite
|
Sign up to set email alerts
|

Neurolocomotor Behavior and Oxidative Stress Markers of Thiazole and Thiazolidinedione Derivatives against Nauphoeta cinerea

Abstract: Thiazolidine compounds NJ20 {(E)-2-(2-(5-bromo-2-methoxybenzylidene)hydrazinyl)-4-(4-nitrophenyl)thiazole} and NW05 [(2-(benzo (d) (1,3) dioxol-4-ylmethylene)-N-(4-bromophenyl)-thiosemicarbazone] potentiated the effect of norfloxacin in resistant bacteria; however, there are no reports on their effects on Nauphoeta cinerea in the literature. The objective of this work was to evaluate the behavioral effects and oxidative markers of NW05 and NJ20 in lobster cockroach N. cinerea. To evaluate the behavioral study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
(76 reference statements)
1
2
0
Order By: Relevance
“…Indeed, substances capable of chelating free iron are categorized as antioxidant compounds, broadly used in toxic-pharmacological studies (Karthik et al, 2016;Schneider et al, 2019). Similar to our results, Pereira et al (2022) reported a significant reduction in Fe 2+ ion content in connective tissue homogenates of N. cinerea after treatment with Thiazolidine compounds NW05 (10 mM) e NJ20 (10 mM). The authors justified that certain thiazoles have excellent free Fe 2+ chelating capacity and moderate toxicity, which corroborates our findings with regard to the antioxidant properties of P. cupana, whose powder decoction…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Indeed, substances capable of chelating free iron are categorized as antioxidant compounds, broadly used in toxic-pharmacological studies (Karthik et al, 2016;Schneider et al, 2019). Similar to our results, Pereira et al (2022) reported a significant reduction in Fe 2+ ion content in connective tissue homogenates of N. cinerea after treatment with Thiazolidine compounds NW05 (10 mM) e NJ20 (10 mM). The authors justified that certain thiazoles have excellent free Fe 2+ chelating capacity and moderate toxicity, which corroborates our findings with regard to the antioxidant properties of P. cupana, whose powder decoction…”
Section: Discussionsupporting
confidence: 89%
“…For this purpose, a simple camera was used for a period of 10 minutes. In sequence, the videos were converted to AVI format and their resolution was reduced to 320 x 240 pixels by using the Any Video Converter Software (Pereira et al, 2022).…”
Section: Sample Preparation For Locomotor and Exploratory Assaysmentioning
confidence: 99%
See 1 more Smart Citation